The Impact of Bulgarian Caretaker Governments Between 2021-2023 on the State Economy - Beev, Ivaylo; Nedelcheva, Yoana (Research Papers, 2025)
In their work “The Economic Effect of Constitutions”, Persson and Tabellini conclude that the constitution directly affects the economic relations in a given country. The study develops the idea that the actions of the Bulgarian caretaker governments of Stefan Yanev (May – December 2021) and Galab Donev (July 2022 – June 2023), as a consequence of a parliamentary crisis and tools in the hands of the head of state, do not exert specific influence on the macroeconomic dynamics in the country—such as is characteristic of regular cabinets in presidential republics. In other words, the caretaker cabinets do not transform economic policy in such a way that one could speak of the establishment of quasi-presidential governance (in an economic sense). Building on the dependencies that Persson and Tabellini identify between the economy and the constitution in presidential and parliamentary republics, the research concludes that the caretaker cabinets in Bulgaria align with the already established direction of economic development set by the regular cabinets of a parliamentary nature.